On the uneven distribution of innovative capabilities and why that matters for research, extension and development policies - Ekboir, Javier; Muñoz, Manrrubio; Aguilar, Jorge; Rendón Mendel, Roberto; García Muñiz, Jose G.; Cárdenas, Altamirano; Reyes, J. (International Food Policy Research Institute, 2006)
Agricultural development policies and programs, including extension and support for innovation, implicitly assume that the whole target population has the ability to innovate. Recent research in neuroscience, education, social sciences and psychology has shown that innovative capabilities are distributed very unevenly. We explored the distribution of innovative capabilities and the ability to integrate a technological package in a sample of commercial lemon producers in Mexico. We have found that the ability to explore new techniques is different from the ability to integrate an efficient production and commercial package. The ability to explore follows an exponential distribution while integration of the package follows a bimodal distribution. The ability to explore depends on the farmer’s connection to a variety of information sources, but not to his/her ability to integrate a technical package. Exploration is also not linked to education, age or credit access. Integration of a production package, on the other hand, depends on more traditional variables such as credit access. These findings have important implications for the design of development programs, including extension and participatory research.